Cold expansion of rail-end-bolt holes: Finite element predictions and experimental validation by DIC and strain gauges. (August 2021) - Pucillo, Giovanni Pio; Carrabs, Alessandro; Cuomo, Stefano; Elliott, Adam; Meo, Michele
Highlights: First study on cold expansion of rail-end-bolt holes with strain gauges and 2D-DIC. Two experimental methods to validate FE simulation of cold expansion of rail holes. Strain-time histories acquired along radial paths during the entire CE process. FE model validation by experimental comparison with maximum and residual strains. Abstract: This paper provides experimental validation of a FE model simulating the cold-expansion of rail-end-bolt holes. Three rail holes were used for the experiments and, contrary to literature, hoop and radial strains were measured along different radial paths during the entire process using both electrical strain gauges and 2D-Digital Image Correlation. Residual and maximum strains predicted with the FE model agree well with measurements obtained with both experimental techniques, providing good confidence in the use of the proposed model to predict the effective stresses acting around the holes and to develop a LEFM-based model for crack growth simulation at cold-expanded holes.